Transient performance of a PCM-based heat sink with a partially filled metal foam: Effects of the filling height ratio. (5th January 2018) - Zhu, Zi-Qin; Huang, Yuan-Kai; Hu, Nan; Zeng, Yi; Fan, Li-Wu
Highlights: A metal foam was partially filled to improve performance of a PCM-based heat sink. Transient performance of the heat sink was tested in terms of filling height ratio. Pore size and heating power effects were also examined as two influencing factors. Filling effectiveness was defined to assess trade-off between performance and cost. Better comprehensive performance can be attained using partial filling strategy. Abstract: In this Short Communication, the transient performance of a phase change material (PCM)-based heat sink filled with a copper foam was experimentally studied. Attention was paid to revealing the influence of filling height ratio of the copper foam on the performance. The effects of pore size of the copper foam and the heating power were also studied parametrically. The results showed that the PCM-based heat sink could inhibit the temperature excursions during the heating period, and that the performance could be improved almost monotonously with increasing the filling height ratio. However, the performance improvement was found to become saturated approaching the full-filling case, regardless of the pore size and heating power. A new parameter, i.e., the filling effectiveness, was defined to help make a trade-off analysis between the performance gain and cost saving. As can be assessed by the filling effectiveness, the 2/3 partial filling was demonstrated to be more economical than full filling because the save in cost of materials and system weight is obvious with only a negligible sacrifice in the gain of performance improvement. The results suggested that the partial filling strategy can be applied to attain a better comprehensive performance of PCM-based heat sinks.